Epidemiology of suicidal ideation, suicide attempts, and direct self-injurious behavior in adolescents with a migration background: a representative study - Carolin Donath; Marie Christine Bergmann; Sören Kliem; Thomas Hillemacher; Dirk Baier (BMC, 2019)
Abstract Background Data on the prevalence of suicidal ideation, suicide attempts, and direct self-injurious behavior in adolescents with a migration background are scarce. There are hints that this population is at risk. The aim of the study is to investigate the epidemiology of suicidal ideation, suicide attempts, and direct self-injurious behavior in adolescents with a migration background in Germany while taking gender-specific differences into consideration. Methods A representative study with N = 10,638 students (mean age 14.91 years, SD = .73).) in the state of Lower Saxony in Germany was conducted. In the 2014-2015 school year, 672 classes were selected by randomly sampling different school types. The participation rate was 84.1%, excluding any classes for which the director refused to provide consent. A total of 49.8% were female adolescents, and 23.3% of the participants had a migration background. Target variables were assessed with items from the Ottawa Self-Injury Inventory, the Self-Harm Behavior Questionnaire and the Self-Harm Inventory, partly adapted. Results Of all students, 7.6% had a lifetime history of suicide attempts, and 36.6% answered with a rating of at least "rarely" when asked to rate the lifetime prevalence of suicidal ideation. The 12-month prevalence of direct self-injurious behavior was 17.8%. Adolescents with a migration background showed a significantly higher prevalence of all three constructs (p = .006; p < .001; p = .006). Male students with a migration background reported a significantly higher lifetime prevalence of suicide attempts (4.7% vs. 3.1%) than native males (p = .009). Female students with a migration background reported a significantly higher lifetime prevalence of suicide attempts (15.9% vs. 10.4%) and suicidal ideation ("often" 12.1% vs. 8.9%) than native female students (p < .001; p = .008). Conclusion Our assessment indicates an elevated risk for suicidal behaviors in adolescents with a migration background. From research on adults, it is known that the dominant motives for suicidal behavior in migrants are associated with their migration history/situation. As suggested by Cramer and Kapusta's (Front Psychol 8:1756, 2017) theoretical model, the Social-Ecological Framework of Theory, Assessment, and Prevention, there is a need for culturally sensitive preventions that take into account the specific reasons for suicide attempts in migrants.